Examination of spotted sand bass (Paralabrax maculatofasciatus) pollutant bioaccumulation in San Diego Bay, San Diego, California - Chad L. Loflen (PeerJ, 2013)
The spotted sand bass (Paralabrax maculatofasciatus) is an important recreational sport and subsistence food fish within San Diego Bay, a large industrialized harbor in San Diego, California. Despite this importance, few studies examining the species life history relative to pollutant tissue concentrations and the consumptive fishery exist. This study utilized data from three independent spotted sand bass studies from 1989 to 2002 to investigate PCB, DDT, and mercury tissue concentrations relative to spotted sand bass age and growth in San Diego Bay, with subsequent comparisons to published pollutant advisory levels and fishery regulations for recreational and subsistence consumption of the species. Subsequent analysis focused on examining temporal and spatial differences for different regions of San Diego Bay.Study results for growth confirmed previous work, finding the species to exhibit highly asymptotic growth, making tissue pollutant concentrations at initial take size difficult if not impossible to predict. This was corroborated by independent tissue concentration results for mercury, which found no relationship between fish size and pollutant bioaccumulation observed. However, a positive though highly variable relationship was observed between fish size and PCB tissue concentration.Despite these findings, a significant proportion of fish exhibited pollutant levels above recommended state recreational angler consumption advisory levels for PCBs and mercury, especially for fish above the minimum take size, making the necessity of at-size predictions less critical. Lastly, no difference in tissue concentration was found temporally or spatially within San Diego Bay.